Students’ Perceptions of Premarital Sexual Behavior and its Implications for Guidance Counseling Services at SMKN 9 Padang - Sevira Listia Andini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to identify students' perceptions of premarital sexual behavior and its implications for counseling services at SMK N 9 Padang. The research method used in this study is descriptive quantitative with a survey approach. The research population consists of 463 students of class XI enrolled in the 2024/2025 academic year, with a sample of 215 students selected using proportionate stratified random sampling. This study aims to measure the following aspects: 1) knowledge about premarital relationships, 2) attitudes towards premarital relationships, and 3) actions related to premarital relationships. The instrument used for data collection in this study is a Likert scale questionnaire. Data analysis was conducted using SPSS 29 statistical software and Microsoft Excel. Based on data analysis, the hypothesis results show that 9 students fall into the very low category with a percentage of 4.2%. Then, 80 students fall into the low category with a percentage of 37.2%. Furthermore, in the fairly high category, there are 114 students with a percentage of 53%, and 12 students in the high category with a percentage of 5.6%. Thus, the majority of students at SMK N 9 Padang fall into the fairly high category with a percentage 53%.